2018
DOI: 10.3233/trd-180020
|View full text |Cite
|
Sign up to set email alerts
|

Extending the phenotypic spectrum of Sengers syndrome: Congenital lactic acidosis with synthetic liver dysfunction

Abstract: Sengers syndrome is a rare autosomal recessive mitochondrial disease characterized by lactic acidosis, hypertrophic cardiomyopathy and bilateral cataracts. We present here a case of neonatal demise, within the first day of life, who initially presented with severe lactic acidosis, with evidence of both chorioamnionitis and cardiogenic shock. Initial metabolic labs demonstrated a severe lactic acidosis prompting genetic testing which revealed a homozygous pathogenic variant for Sengers syndrome in AGK, c.979A >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…All rights reserved Sengers syndrome is an autosomal recessive disorder characterised by congenital cataracts, hypertrophic cardiomyopathy, skeletal myopathy and lactic acidosis ( Table 1) [ [107][108][109][110][111][112][113][114][115]. Sengers syndrome is caused by a variety of mutations in the TIM22 complex component AGK, including missense, nonsense and frameshift mutations [107][108][109][110][111][112][113][114][115]. The severity of the phenotype varies significantly, even within families with the same mutation, although it should be noted that the less affected sibling in this case received intervention at an early age potentially affecting disease progression [113].…”
Section: Accepted Articlementioning
confidence: 99%
“…All rights reserved Sengers syndrome is an autosomal recessive disorder characterised by congenital cataracts, hypertrophic cardiomyopathy, skeletal myopathy and lactic acidosis ( Table 1) [ [107][108][109][110][111][112][113][114][115]. Sengers syndrome is caused by a variety of mutations in the TIM22 complex component AGK, including missense, nonsense and frameshift mutations [107][108][109][110][111][112][113][114][115]. The severity of the phenotype varies significantly, even within families with the same mutation, although it should be noted that the less affected sibling in this case received intervention at an early age potentially affecting disease progression [113].…”
Section: Accepted Articlementioning
confidence: 99%
“…The clinical manifestation of Sengers syndrome closely resembles that of mitochondrial ATP synthesis disorder and cardiolipin metabolism deficiency. The predominant symptoms of the disease are congenital cataracts, hypertrophic cardiomyopathy, skeletal myopathy, exercise intolerance, and lactic acidosis (Mayr et al, 2012;Beck et al, 2018). Patients with severe cases die in infancy, while people with mild cases can survive for decades (Haghighi et al, 2014).…”
Section: Agk and Sengers Syndromementioning
confidence: 99%
“…An increasing number of reports have investigated families with Sengers syndrome and via whole-exome sequencing identified different types of mutations in the AGK gene, and patients with different AGK mutations show clinical heterogeneity (Mayr et al, 2012;Siriwardena et al, 2013;Haghighi et al, 2014;Beck et al, 2018;Aggarwal et al, 2021). Adenine nucleotide transporter 1 (ANT1, also known as SLC25A4) is a mitochondrial protein with dual functions.…”
Section: Agk and Sengers Syndromementioning
confidence: 99%
“…Supplementary Material 1 | Gene structure of AGK and localization of identified mutations (1)(2)(3)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Red font indicates newly reported mutations.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The AGK gene is located on chromosome 7q34 and consists of 16 exons (1). To date, several studies have identified different types of loss-of-function mutations in the AGK gene, including start codon mutations, nonsense, frameshift, and splice site mutations (1)(2)(3)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). AGK is a mitochondrial protein that catalyzes the phosphorylation of diacylglycerol (DAG) and monoacylglycerol (MAG) to phosphatidic acid (PA) and lysophosphatidic acid (LPA), respectively.…”
Section: Introductionmentioning
confidence: 99%